1997
DOI: 10.1046/j.1365-2109.1997.t01-1-00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced spawning in bream, Abramis brama (L.), using carp and bream pituitary extract and hCG

Abstract: Induced spawning in bream, Abramis brama (L), was studied using acetone‐dried common carp pituitary (CP) and bream pituitary (BP) with or without the addition of human chorionic gonadotrophin (hCG). The total dose administered to fish was of 5.0 mg kg−1 BP or 4.0 mg kg−1 CP with or without 2000‐2200 IU hCG kg−1 for females and 2.5 mg kg−1 BP or 2.0 mg kg−1 CP with or without 1000–1100 IU HCG kg−1 for males. In all male treated groups 100% of spermiation was observed: in females the most effective method was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
34
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 10 publications
5
34
0
3
Order By: Relevance
“…For this reason many hormonal treatments are used to stimulate gamete maturation in commercial cyprinids. One of the most commonly applied spawning agents is carp pituitary extract (CPE) (Yaron et al, 1984;Thalathiah et al, 1988), in same cases with addition of human chorionic gonadotropin (hCG) (Kucharczyk et al, 1997a). The good results of induced ovulation in cyprinid fish were also obtained after hormonal stimulation by a synthetic analogue of gonadotropin-releasing hormone (GnRH), frequently with strong dopamine antagonists (Yaron, 1995;Barth et al, 1997).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason many hormonal treatments are used to stimulate gamete maturation in commercial cyprinids. One of the most commonly applied spawning agents is carp pituitary extract (CPE) (Yaron et al, 1984;Thalathiah et al, 1988), in same cases with addition of human chorionic gonadotropin (hCG) (Kucharczyk et al, 1997a). The good results of induced ovulation in cyprinid fish were also obtained after hormonal stimulation by a synthetic analogue of gonadotropin-releasing hormone (GnRH), frequently with strong dopamine antagonists (Yaron, 1995;Barth et al, 1997).…”
mentioning
confidence: 99%
“…Injections of hCG were intramuscular in the dorsal region of the body (Thalathiah et al, 1988). Injections of pituitary (Kucharczyk et al, 1997a) and ovopel (Horvath et al, 1997) extracts were intraperitoneal at the base of the pelvic fin. Before manipulations fish were anaesthetised with 2-phenoxyethanol (0.5 ml per l).…”
Section: Hormonal Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the doses used in this protocol is shown in Table 1. The use of hCG combined with pituitary extracts has been used in fish species (Thalathiah et al, 1988;Kucharczyk et al, 1997;Zohar & Mylonas, 2001;Leonardo et al, 2004) and has proven to be a very successful and consistent strategy in catfish species (Thalathiah et al, 1988).…”
mentioning
confidence: 99%
“…Jamiński (2005) also observed a high percentage of females from line 7 ovulating after treatment with Ovopel (90 %). The author indicated that the spawning effectiveness coefficient (Se; Kucharczyk et al 1997) for line 7 was considerably lower compared to the French line F and the Lithuanian lines B and V. Cejko (2007) indicated that within line 7, the percentage of ovulating females was higher after hypophysation than after treatment with Ovopel, whereas the egg weight expressed in grams and as a percentage of female body weight was higher after stimulation with Ovopel (the quality of eggs obtained after treatment with each of the stimulators did not vary). Białowąs et al (2008) reported a very low percentage of ovulating female (35-45 %) in line 7 and a very low relative fecundity for this line, namely 80-90 (thousand eggs/ kg -1 female body weight).…”
Section: Discussionmentioning
confidence: 99%